The Experiences of Late-diagnosed Women with Autism Spectrum Conditions: An Investigation of the Female Autism Phenotype - Bargiela, Sarah; Steward, Robyn; Mandy, William (Journal of autism and developmental disorders, 2016)
We used Framework Analysis to investigate the female autism phenotype and its impact upon the under-recognition of autism spectrum conditions (ASC) in girls and women. Fourteen women with ASC (aged 22–30 years) diagnosed in late adolescence or adulthood gave in-depth accounts of: ‘pretending to be normal’; of how their gender led various professionals to miss their ASC; and of conflicts between ASC and a traditional feminine identity. Experiences of sexual abuse were widespread in this sample, partially reflecting specific vulnerabilities from being a female with undiagnosed ASC. Training would improve teachers’ and clinicians’ recognition of ASC in females, so that timely identification can mitigate risks and promote wellbeing of girls and women on the autism spectrum.